Get reliable answers to your questions at Westonci.ca, where our knowledgeable community is always ready to help. Our Q&A platform provides quick and trustworthy answers to your questions from experienced professionals in different areas of expertise. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
To determine the value of [tex]\( x \)[/tex] that makes [tex]\(\overline{KM} \parallel \overline{JN}\)[/tex], we can use the converse of the side-splitter theorem. According to this theorem, if [tex]\(\frac{JK}{KL} = \frac{JM}{MN}\)[/tex], then [tex]\(\overline{KM} \parallel \overline{JN}\)[/tex]. In this context, substituting the given expressions:
[tex]\[ \frac{JK}{KL} = \frac{x-5}{x} \quad \text{and} \quad \frac{JM}{MN} = \frac{x-3}{x+4} \][/tex]
Step-by-step solution:
1. By the converse of the side-splitter theorem, if [tex]\(\frac{JK}{KL} = \frac{x-5}{x} = \frac{JM}{MN} = \frac{x-3}{x+4}\)[/tex], then [tex]\(\overline{KM} \parallel \overline{JN}\)[/tex].
2. Substitute the expressions into the proportion:
[tex]\[ \frac{x-5}{x} = \frac{x-3}{x+4} \][/tex]
3. Cross-multiply:
[tex]\[ \text{Cross-multiply: } (x-5)(x+4) = x(x-3) \][/tex]
4. Distribute both sides:
[tex]\[ x(x) + x(4) - 5(x) - 5(4) = x(x) + x(-3) \][/tex]
5. Multiply and simplify:
[tex]\[ x^2 + 4x - 5x - 20 \sim x^2 - 3x \][/tex]
[tex]\[ x^2 - x - 20 \sim x^2 - 3x \][/tex]
6. To find [tex]\( x \)[/tex], combine and simplify the terms:
[tex]\[ x^2 - x - 20 = x^2 - 3x \][/tex]
[tex]\[ 0 = 2x - 20 \][/tex]
7. Solve for [tex]\( x \)[/tex]:
[tex]\[ 2x - 20 = 0 \][/tex]
[tex]\[ 2x = 20 \][/tex]
[tex]\[ x = 10 \][/tex]
Therefore, the value of [tex]\( x \)[/tex] that makes [tex]\(\overline{KM} \parallel \overline{JN}\)[/tex] is [tex]\( \boxed{10} \)[/tex].
[tex]\[ \frac{JK}{KL} = \frac{x-5}{x} \quad \text{and} \quad \frac{JM}{MN} = \frac{x-3}{x+4} \][/tex]
Step-by-step solution:
1. By the converse of the side-splitter theorem, if [tex]\(\frac{JK}{KL} = \frac{x-5}{x} = \frac{JM}{MN} = \frac{x-3}{x+4}\)[/tex], then [tex]\(\overline{KM} \parallel \overline{JN}\)[/tex].
2. Substitute the expressions into the proportion:
[tex]\[ \frac{x-5}{x} = \frac{x-3}{x+4} \][/tex]
3. Cross-multiply:
[tex]\[ \text{Cross-multiply: } (x-5)(x+4) = x(x-3) \][/tex]
4. Distribute both sides:
[tex]\[ x(x) + x(4) - 5(x) - 5(4) = x(x) + x(-3) \][/tex]
5. Multiply and simplify:
[tex]\[ x^2 + 4x - 5x - 20 \sim x^2 - 3x \][/tex]
[tex]\[ x^2 - x - 20 \sim x^2 - 3x \][/tex]
6. To find [tex]\( x \)[/tex], combine and simplify the terms:
[tex]\[ x^2 - x - 20 = x^2 - 3x \][/tex]
[tex]\[ 0 = 2x - 20 \][/tex]
7. Solve for [tex]\( x \)[/tex]:
[tex]\[ 2x - 20 = 0 \][/tex]
[tex]\[ 2x = 20 \][/tex]
[tex]\[ x = 10 \][/tex]
Therefore, the value of [tex]\( x \)[/tex] that makes [tex]\(\overline{KM} \parallel \overline{JN}\)[/tex] is [tex]\( \boxed{10} \)[/tex].
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.